Food Insecurity and Dietary Intake Among Elderly Population: A Systematic Review - Maryam Zarei; Mostafa Qorbani; Shirin Djalalinia; Norhasmah Sulaiman; Thambiah Subashini; Geeta Appanah; Ebrahim Khalil Naderali (International Journal of Preventive Medicine, 2021)
Background: This review seeks to determine the relationship between food insecurity among elderly people over the past decades and nutrient deficiency, which is rather unclear. We aim to systematically review the relationship between food insecurity and dietary intake among elderly population. Methods: In this systematic review, we systematically searched the international databases including PubMed, Web of Sciences, and Scopus for scientifically related papers which have been published up until January 2018. For a more refined search, we used the Medical Subject Headings (MeSH) terms and Emtree. In terms of search protocol, no restrictions were placed on time and language. Two independent reviewers conducted the data refining processes. Validated form (PRISMA) was used to conduct quality assessment and data extraction. Results: Eight cross sectional studies have been included in this review. Two of the studies were conducted in Asia and the remaining six studies were largely based in the United States and Canada. Food insecurity was associated with low levels of vitamin and mineral intakes such as vitamins E, A, B, and D and also zinc, calcium, magnesium, and iron. Most studies also reported insufficient energy, and micro and macronutrients intake among elderly people. Conclusions: The findings of this review evidence a considerable amount of food insecurity and nutrient deficiency, including vitamins E, C, D, B 2, and B 12 and zinc, phosphorus, and calcium among elderly population. These findings could be used as reliable evidence by policy makers and future complementary analyses.